Hyaluronic Acid and Wound Healing - Neuman, Manuela G; Nanau, Radu M; Oruña-Sanchez, Loida; Coto, Gabriel (Journal of Pharmacy & Pharmaceutical Sciences, 2015)
Background. We developed an experimental model of ethanol-induced dermatotoxicity and hepatocytoxicity using normal human keratinocytes and normal human hepatocytes that preserve inducible cytochrome p450 activities. The original work was described in several articles. The objective of this study was to determine whether hyaluronic acid attenuates skin necrosis, and to further clarify its uses in wound repair in humans, animal models and in vitro studies. Methods. We performed a systematic review of the literature using the terms “hyaluronic acid” and “wound healing”. PubMed was searched for studies published during the period 2010-2014. Results. Hyaluronic acid is used in tissue regeneration alone or in combination with herbal or Western medicine. Scaffolds made up of hyaluronic acid were used to embed basic fibroblast growth factor. Conclusion. Hyaluronic acid extracts are safe and efficacious products to be used in skin repair. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.